St. Philaret of Moscow and the “governmental sphere” in the reign of emperor Alexander II - Georgy Bezhanidze; Andrey Firsov (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2023)
The article is devoted to the analysis of the participation of the Metropolitan of Moscow Filaret (Drozdov) in the development of government policy measures during the period of the Great Reforms. Saint Philaret (Drozdov), the most authoritative hierarch of the Russian Church, by the beginning of the reign of Emperor Alexander II, had considerable experience in ecclesiastical and political activity. He had been familiar with the monarch who had ascended the throne for a long time, their relationship was not only official, but also personal. The emperor's wife, Maria Alexandrovna, respected the spiritual gifts of the Moscow Metropolitan. Faced with the problem of writing the text of the manifesto on the abolition of serfdom, the government turned to Metropolitan Philaret. The Moscow saint formulated his own, different from the original, concept of the content of the document, which was accepted. Less well known is his involvement in the preparation of the budget reform. The article reveals the role of the metropolitan in the legislative recognition of a special status for church finances, different from both state and public funds. Some reform initiatives of the government were not implemented due to the opposition of the metropolitan. The active position of St. Philaret prevented the liberalization of the policy towards the Old Believer schism. By rejecting the idea of including a hierarchy in the Council of State, he contributed to the emperor's abandonment of constitutional undertakings. Thus, Metropolitan Filaret (Drozov) should be regarded not only as a prominent church hierarch, but also as a prominent participant in government activities during the era of the Great Reforms.